The effect of using the cognitive model (Paradigm) in reducing psychological stress among football players at Al-Mustansiriya University - Zubair, Ari; Falih, Zainab (Humanities Journal of University of Zakho, 2022)
It is known that there are three main aspects of the human personality, namely the cognitive aspect, the emotional side and the skilled aspect. These three aspects of the human personality should be built so that we can create an integrated and balanced human personality, cognitively, emotionally and maharia. In light of this, the construction process should proceed in parallel, continuous and integrated with each other, because any defect in any of these aspects will create an unbalanced and fully developed human personality properly and therefore not be effective and influential in the social construction of society. . Paradigm is a way to talk about the individual’s feelings about himself, about others and about the world around him, as well as about things that affect his feelings and ideas . That is, it is a treatment that focuses on the present rather than on past causes that may be the cause of these symptoms on the player and therefore a treatment to improve her psychological state.. . The problem of research is that there are a lot of circumstances that the player goes through that result in a lot of psychological, social and economic problems that lead to the emergence of psychological pressures in the football player, so the researchers decided to use the cognitive model (Paradigm) in reducing the psychological pressures of football players. . The research aims to: 1- Identifying the cognitive model (Paradigm) in reducing the psychological pressures of footballers. 2- Using paradigm in reducing the psychological pressures of footballers. The search duties were:. There are statistically significant differences between the grades of the pilot group and the ranks of the control group in the psychological pressure scale of the tribal test. 2- There are statistically significant differences between tribal testing and remote testing of the grades of the experimental group and the control group in the psychological pressure scale and in favor of the experimental group. There are statistically significant differences between the grades of the experimental group and the ranks of the control group in the psychological pressure scale (after the application of the cognitive model The research community included the football players at the University of Mustansiriyah/ and the number of (120) players participating in the University Of Mustansiriyah Football Championship representing (7) colleges, which are the sample of the answer to the questionnaire, while the sample of the research amounted to (20) players of the Faculty of Physical Education and Sports Sciences by (10) players for the experimental group and (10) players for the control group selected in the random way either and selected (5) players for the reconnaissance experiment. . The researchers used the psychological pressure scale from a similar research which contains (30) paragraphs and (5) alternatives and the scientific foundations of psychological measures the researcher conducted a reconnaissance experiment according to the results of the tribal tests of the research sample where the curriculum was built for (8 weeks) by two units per week to be the total number of units (16 units). The duration of the guidance unit ranged from (20 minutes to 30 minutes) The cognitive model is generally aimed at relieving the psychological pressures of football players, accustoming the members of the research sample to patterns of positive thinking and moving away from negative thinking that leads to symptoms of psychological stress. The remote test of the research sample was then conducted and the researchers used the SPSS statistical bag to extract the results of the research and after presenting, discussing and analyzing the results and in the light of the results that were drawn with the following conclusions: The differences were significant in the tribal testing of the control and experimental groups in the psychological pressure scale prior to the implementation of the programme 2- Non-statistically significant differences appeared in the remote test and in favor of the experimental group in the measure of psychological stress after the application of the cognitive model (Paradigm) in reducing the psychological pressures of football players in the University of Mustansiriyah 3- Paradigm has contributed to reducing the psychological pressures of football players at the University of Mustansiriyah. For the benefit of the experimental group.